Development of mucosal‐associated invariant T cells. Issue 6 (24th April 2018) - Koay, Hui‐Fern; Godfrey, Dale I; Pellicci, Daniel G
Abstract: Mucosal‐associated invariant T (MAIT) cells develop in the thymus and migrate into the periphery to become the largest antigen‐specific αβ T‐cell population in the human immune system. However, the frequency of MAIT cells varies widely between human individuals, and the basis for this is unclear. While MAIT cells are highly conserved through evolution and are phenotypically similar between humans and mice, they represent a much smaller proportion of total T cells in mice. In this review, we discuss how MAIT cells transition through a three‐stage development pathway in both mouse and human thymus, and continue to mature and expand after they leave the thymus. Moreover, we will explore and speculate on how specific factors regulate different stages of this process. Abstract : Mucosal‐associated invariant T cells represent the largest population of T cells with a single specificity in the human immune system. This article reviews how MAIT cells develop in mice and humans.